Assessing the policy environment for digital connectivity and accessibility in the Asia-Pacific region - Witada Anukoonwattaka; Natnicha Sutthivana; Yann Duval (Asia-Pacific Research and Training Network on Trade (ARTNeT), 2024)
The digital connectivity in the Asia-Pacific region is primarily shaped by the availability of ICT infrastructure, the nature of regulatory policies, and the dynamics of competition among service providers. This paper explores the policies and regulations that affect the costs and accessibility of digital infrastructure in the 21 Asia-Pacific economies included in the ESCAP's Regional Digital Trade Integration (RDTII) Database: Australia, Brunei Darussalam, Cambodia, India, Indonesia, Japan, Kazakhstan, Lao People's Democratic Republic (PDR), Malaysia, Nepal, New Zealand, Pakistan, the Philippines, the Republic of Korea, the Russian Federation, Singapore, Thailand, Türkiye, Vanuatu, Viet Nam, and Hong Kong, China. It specifically focuses on trade and investment policies, as well as regional cooperation initiatives in Asia and the Pacific, that have an impact on (1) telecommunications infrastructure and services, and (2) ICT products. Despite trends towards liberalization, the telecom and ICT sectors in Asia-Pacific economies are generally found to be heavily regulated. The predominance of state monopolies and diverse regulatory approaches across different economies potentially result in high digital connectivity costs and a lack of a competitive environment. This potentially contributes to a significant divide in digital infrastructure quality and accessibility observed across the region.
hdl:20.500.12870/7108
Keywords: F13; F23; L43; L52; L86; L96; K33; O38; Q01; 330; digital connectivity; telecommunication services; digital divide; Asia-Pacific; digital trade; investment